Cylindrically symmetric diffusion model for relativistic heavy-ion collisions - Hölck, Johannes; Wolschin, Georg (Annalen der Physik, 2024)
A relativistic diffusion model with cylindrical symmetry, which propagates an initial state based on quantum chromodynamics in time toward a thermal equilibrium limit, is derived from nonequilibrium-statistical considerations: adapting an existing framework for Markovian stochastic processes representing relativistic phase-space trajectories, a Fokker-Planck equation is obtained for the time evolution of particle-number distribution functions with respect to transverse and longitudinal rapidity. The resulting partially-evolved distribution functions are transformed to transverse-momentum and pseudorapidity space, and compared with charged-hadron data from the CERN Large Hadron Collider.
Zuerst veröffentlicht: 07. März 2024
Gesehen am 11.07.2024